Impulse control disorders and behavioural addictions in the ICD-11 - Grant, Jon E.; Atmaca, Murad; Fineberg, Naomi A.; Fontenelle, Leonardo F.; Matsunaga, Hisato; Reddy, Y. C. Janardhan; Stein, Dan J. (Wiley, 2014)
[Abstract Not Available]